Frequency of vitamin D deficiency in children with iron deficiency anaemia and factors associated with vitamin D deficiency - Abdul Razzaq, Ayesha; Haider, Nighat; Faiz , Abida; Naseer, Maryam; Waheed, Nadia; Siddiqui, Hina Batool (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate vitamin D deficiency in children with iron-deficiency anaemia, and to identify the risk factors for such deficiency. Method: The cross-sectional study was conducted at the Children’s Hospital, Pakistan Institute of Medical Sciences, Islamabad, Pakistan, from October 2021 to March 2022, and comprised children aged 1-5 years who had been diagnosed with iron-deficiency anaemia. Quantitative variables, like age, height, weight, gender, socioeconomic status and sibling status, were controlled by stratification. Data was compared to assess the risk factors of vitamin D deficiency among the subjects. Data was analysed using SPSS 22. Results: Of the 236 children with iron-deficiency anaemia, 159(67.5%) also had vitamin D deficiency; 95(59%) girls and 65(41%) boys. Overall, 104(65.4%) subjects were aged 4-5 years and 55(34.6%) were aged 1-3 years. Vitamin D deficiency had significant association with female gender, older age, height and weight <5th centiles, educated parents, low to middle socioeconomic status, urban residence and higher number of siblings (p<0.05). Conclusion: The prevalence of vitamin D deficiency among children with iron-deficiency anaemia was found to be high. Key Words: Anaemia, IDA, Vitamin D deficiency, Micronutrients deficiency, Risk factors.